News or noise: Mobile internet technology and stock market activity - Nerissa C. Brown; W. Brooke Elliott; Russ Wermers; Roger M. White (University of Cologne, Centre for Financial Research (CFR), 2021)
Mobile internet devices reduce trading frictions and information search costs for investors, but also introduce attention-competing activities,such as social networking. We use exogenous nationwide and city-level outages of the Blackberry Internet Service (BIS) to investigate the effect of mobile internet technology on investors'information-gathering vs. attention-diverting activities. We find that trading volume and trading frequency surge by about 5% on days when mobile internet systems go dark, consistent with a greater role for devices (when not dark) in diverting the limited attention of investors away from information-gathering and trading - even when they are used by presumably more sophisticated investors.
Keywords: D83; G12; G14; L86; 330; mobile technology; investor activity; stock market liquidity; limited attention; distraction